Platform work and the employment relationship - Valerio De Stefano; Ilda Durri; Charalampos Stylogiannis; Mathias Wouters (International Labour Organization (ILO), 2021)
This working paper analyses national and supranational case law and legislation about the employment status of platform workers. It does so by referring to the ILO Employment Relationship Recommendation, 2006 (No. 198). It finds that this Recommendation provides for a valuable compass to navigate the issues that emerge from the analysis of the existing case law and legislation about platform work.
Keywords: 330; non-standard forms of employment; digital labour; labour contracts; telework; work at home; labour legislation; gig economy; information and communication technologies